Pharmacokinetics of tulathromycin in fetal sheep and pregnant ewes. Issue 4 (17th January 2019) - MacKay, Evelyn E.; Washburn, Kevin E.; Padgett, Ashley L.; Fajt, Virginia R.; Lo, Chih‐Ping; Mays, Travis P.; Washburn, Shannon E.
Abstract: Macrolides are important antimicrobials frequently used in human and veterinary medicine in the treatment of pregnant women and pregnant livestock. They may be useful for the control of infectious ovine abortion, which has economic, animal health, and human health impacts. In this study, catheters were surgically placed in the fetal vasculature and amnion of pregnant ewes at 115 (±2) days of gestation. Ewes were given a single dose of 2.5 mg/kg tulathromycin subcutaneously, and drug concentrations were determined in fetal plasma, maternal plasma, and amniotic fluid at 4, 8, 12, 24, 36, 48, 72, 144, and 288 hr after drug administration. Pharmacokinetic parameters in maternal plasma were estimated using noncompartmental analysis and were similar to those previously reported in nonpregnant ewes. Tulathromycin was present in fetal plasma and amniotic fluid, indicating therapeutic potential for use against organisms in these compartments, though concentrations were lower than those in maternal plasma. Time‐course of drug concentrations in the fetus was quite different than that in the ewe, with plasma concentrations reaching a plateau at 4 hr and remaining at this concentration for the remainder of the sampling period (288 hr), raising questions about how tulathromycin may be transported into or metabolized and eliminated by the fetus.